2005
DOI: 10.1042/bj20041170
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of artemisinin with haemoglobin: implications for antimalarial activity

Abstract: Elucidation of the principal targets of the action of the antimalarial drug artemisinin is an ongoing pursuit that is important for understanding the action of this drug and for the development of more potent analogues. We have examined the chemical reaction of Hb with artemisinin. The protein-bound haem in Hb has been found to react with artemisinin much faster than is the case with free haem. It appears that the uptake of Hb and the accumulation of artemisinin into the food vacuole, together with the preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 47 publications
1
66
0
4
Order By: Relevance
“…The degradation of artemisinin or Hb reported in previous studies (1,14,21,28,30,38) can most likely be explained by Hb denaturation and subsequent heme release mediated by organic solvents (21), reducing agents (7), or buffers or the use of a higher temperature (11,12,24,34). The stability of peroxide antimalarials with oxyHb is consistent with their antimalarial efficacy in vivo, the absence of toxicity toward healthy erythrocytes, and the notion that free heme or iron is required for peroxide activation and subsequent antimalarial activity.…”
Section: Figsupporting
confidence: 54%
See 1 more Smart Citation
“…The degradation of artemisinin or Hb reported in previous studies (1,14,21,28,30,38) can most likely be explained by Hb denaturation and subsequent heme release mediated by organic solvents (21), reducing agents (7), or buffers or the use of a higher temperature (11,12,24,34). The stability of peroxide antimalarials with oxyHb is consistent with their antimalarial efficacy in vivo, the absence of toxicity toward healthy erythrocytes, and the notion that free heme or iron is required for peroxide activation and subsequent antimalarial activity.…”
Section: Figsupporting
confidence: 54%
“…These studies suggested reduction of the peroxide bond by the bound heme moiety of Hb, resulting in either decreased artemisinin concentration (1) or potency (28), Hb degradation (21), or alkylation of globin (38) or heme (14,30). Inconsistencies are apparent among these findings and are suggested to result from variations in the Hb oxidation state and conformational stability (21).…”
mentioning
confidence: 99%
“…Kannan et al (12) have reported that heme alkylation by artemisinin only marginally decreased the molar extinction coefficient of heme (27% decrease when the solvent was methanol), and it is expected that alkylation by trioxolanes would have a similar effect on absorptivity. The visible absorbance of the alkylated heme product (472 nm) from each active trioxolane in this study was equivalent to 79% (Ϯ 5%) of the decrease in heme absorbance (418 nm), suggesting highly efficient formation of the alkylated adduct.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested (21) that artemisinin may undergo reductive activation in the mitochondria of P. falciparum and thereby inhibit the growth of the parasite. Indeed, in addition to Hb (19,26,34,43), artemisinin alkylates other hemoproteins, such as cytochrome c (43). However, if the mitochondria were the primary plasmodial target of artemisinin (21), it is hard to explain why all other protozoa are so much less sensitive to artemisinin.…”
mentioning
confidence: 99%